The radical rationalization of management thought: Its causes and consequences - P. Human (South African Journal of Business Management, 1986)
Radical rationalization refers to the phenomenon where means are seen as ends-in-themselves. Translated to the practice of management this would mean that the exercise of techniques is absolutized to the extent that ends (goals) are lost from sight. In this article we enquire into the causes as well as the consequences of this phenomenon. It is argued that the nature of science as well as the nature of the bureaucratic organization can be seen as causal factors to the 'iron cage' of radical rationalization. Some of those familiar 'iron cages' such as strategic planning, industrial relations, behaviour modelling and the personal computer are discussed.
Keywords: 650